CompTIA Server+ (SK0-005) - Bryan, Wes; Wong, Ronnie (Packt Publishing, 2023)
The course begins with an exploration of server architecture, delving into components, racks, power management, and connectivity, establishing a solid foundation. You'll gain insight into the types of storage drives, shared storage solutions, and the importance of fault tolerance. The course focuses on hands-on server administration, from OS requirements and installations to robust server network configuration. It emphasizes the significance of server roles, storage management, and data security, linking them to high-availability and cloud technologies. The course wraps up by equipping you with critical skills in scripting, asset management, disaster recovery, and troubleshooting, ensuring you're prepared to tackle server challenges head-on. What you will learn Identify server hardware components Configure network roles and features Implement effective data security measures Perform disaster recovery operations Apply server monitoring techniques Troubleshoot common server issues Audience This course is ideal for IT professionals seeking to advance in server administration. Basic knowledge of computer systems and networks is beneficial. This course is designed for those aiming to align their skills with industry-standard server management and security practices. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Wes Bryan: Wes Bryan embarked on his IT career path in 2009, initially as a mentored learning instructor, and later transitioning into a technical IT instructor. His exceptional teaching skills were recognized with three global teaching awards for 'Global Technical Instructor' during his early teaching years. Wes has made notable contributions as a member of the CIN (CompTIA Instructor Network) Advisory Board and the Board of Directors for CompTIA AITP (Association of Information Technology Professionals). Certifications: CompTIA A+, Network+, Security+, Server+, Cloud+, CySA+; MCSA; MTA; MCTS; MCP; MS; MCT. Ronnie Wong: Ronnie Wong has had a diverse career, from diesel service and ministry to computer repair and network administration in small businesses. He set up networks and servers and created policies in these roles. As an Edutainer at ITProTV, now ACI Learning, he started as an IT technical instructor, later working as a contract trainer for the University of Florida, Marion County School Systems, and Nationwide Insurance. He provided Cisco, Microsoft Windows, CompTIA, and IT security training to military and DoD personnel. Now the Director of Content Development at ACI Learning, Ronnie's credentials include CCNP Enterprise Infrastructure, CCNA, CompTIA's A+, Network+, Security+, ISC2 CC, CNA Security, and PCNSA.
Online resource; title from title details screen (O'Reilly, viewed January 3, 2023)
Keywords: Client/server computing -- Study guides -- Examinations; Web servers -- Study guides -- Examinations; Instructional films; Nonfiction films; Internet videos